2018
DOI: 10.1093/jncics/pky056
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Protein Loss as a Prognostic and Predictive Biomarker in Breast Cancers Regardless of Microsatellite Instability

Abstract: Background Breast cancers that harbor mismatch-repair (MMR) deficiency and/or microsatellite instability (MSI) might be sensitive to immune checkpoint blockade, but there are currently no specific guidelines for assessing MMR status in breast cancer. Here, we sought to define the clinical value of MMR immunohistochemistry (IHC) and MSI analysis in breast cancers. Methods We subjected 444 breast cancers to MMR IHC and MSI anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 45 publications
4
93
2
Order By: Relevance
“…Furthermore, a recent study in 94 HER2-positive luminal B breast cancer patients showed that, although 13.5% of cases had a germline mutation (V384D) in the MLH1 gene, only 3 cases (3.2%) were MLH1-deficient by IHC [37]. In contrast, a recently published cohort from Italy reported a ten-times higher frequency (17%, 75 out of 444 cases) of homogenous MMR loss by immunohistochemistry [30]; although when further investigated by microsatellite instability assay, all but seven of these were negative (meaning only 1.6% of cases overall were MSI positive). The discrepancy in their reported frequency of MMR-deficient cases in breast cancer by IHC could be due to the inclusion of cases which lack an internal positive control.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, a recent study in 94 HER2-positive luminal B breast cancer patients showed that, although 13.5% of cases had a germline mutation (V384D) in the MLH1 gene, only 3 cases (3.2%) were MLH1-deficient by IHC [37]. In contrast, a recently published cohort from Italy reported a ten-times higher frequency (17%, 75 out of 444 cases) of homogenous MMR loss by immunohistochemistry [30]; although when further investigated by microsatellite instability assay, all but seven of these were negative (meaning only 1.6% of cases overall were MSI positive). The discrepancy in their reported frequency of MMR-deficient cases in breast cancer by IHC could be due to the inclusion of cases which lack an internal positive control.…”
Section: Discussionmentioning
confidence: 95%
“…Another limitation of our study is that the determination of MMR loss by IHC is based on its strong correlation with the functionality of MMR rather than direct assessment of DNA mutational patterns. We are aware of the potential misrepresentation, but have found many sources supporting the robustness of IHC compared to genomic methods [19,30]. Some reports suggest there is a tradeoff Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancers, alterations in the expression patterns of the MMR proteins are not exceptional, being observed at a frequency of 2-29%, and have both a prognostic and predictive value [7][8][9][10]. The pathological evaluation of MMR status, however, is controversial in these neoplasms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…During replication, they may suffer errors which are quickly repaired, and normal replication follows. Hence, microsatellite instability (MSI) is the name given to the germline allele portion of the microsatellite that has suffered addition or deletion of its units, product of loss of cell capacity to correct errors associated with replication, resulting in a somatic length alteration [3,11].…”
Section: Introductionmentioning
confidence: 99%